Traffic and highway engineering - Garber, Nicholas J.; Hoel, Lester A. (Cengage Learning, 2015)
This text focuses exclusively on traffic and highway engineering. It includes a discussion of the pivotal role transportation plays in our society, including employment opportunities, historical impact, and the impact of transportation on our daily lives.